Stimulation of neural stem cell proliferation by inhibition of phosphodiesterase 5 - Santos, Ana Isabel (2018)
The involvement of nitric oxide (NO) and cyclic GMP (cGMP) in neurogenesis has been progressively unmasked over the last decade. Phosphodiesterase 5 (PDE5) specifically degrades cGMP and is highly abundant in the mammalian brain. Inhibition of cGMP hydrolysis by blocking PDE5 is a possible strategy to enhance the first step of neurogenesis, proliferation of neural stem cells (NSC). In this work, we have studied the effect on cell proliferation of 3 inhibitors with different selectivity and potency for PDE5, T0156, sildenafil, and zaprinast, using subventricular zone-(SVZ-) derived NSC cultures. We observed that a short-(6 h) or a long-term (24 h) treatment with PDE5 inhibitors increased SVZ-derived NSC proliferation. Cell proliferation induced by PDE5 inhibitors was dependent on the activation of the mitogen-activated protein kinase (MAPK) and was abolished by inhibitors of MAPK signaling, soluble guanylyl cyclase, and protein kinase G. Moreover, sildenafil neither activated ERK1/2 nor altered p27(Kip1) levels, suggesting the involvement of pathways different from those activated by T0156 or zaprinast. In agreement with the present results, PDE5 inhibitors may be an interesting therapeutic approach for enhancing the proliferation stage of adult neurogenesis.